Youth's Sibling Relationships Across the Course of a Parent's Military Deployment: Trajectories and Implications. Issue 6 (24th March 2020) - Whiteman, Shawn D.; Hamwey, Meghan K.; Topp, Dave; MacDermid Wadsworth, Shelley
Abstract : The present exploratory study explored the trajectories and implications of at‐home (military unaffiliated) parents' perceptions of youth's sibling relationships across the course of a parent's military deployment. Participants included 109 families with at least two siblings (older sibling and younger siblings age: M = 10.85, SD = 3.92 and M = 7.89, SD = 3.58, respectively) and one parent serving in the National Guard. Data were collected via in‐home interviews, at six time points across the deployment cycle. A series of multilevel models revealed increases in sibling disharmony during the months a deployed parent was away, but showed signs of recovery in the year after they returned. Increases in sibling disharmony were positively associated with increases in youth's externalizing behaviors above and beyond the effects of parenting.